2017
DOI: 10.1186/s12889-017-4953-9
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index had different effects on premenopausal and postmenopausal breast cancer risks: a dose-response meta-analysis with 3,318,796 subjects from 31 cohort studies

Abstract: BackgroundThere is sufficient evidence supporting a relationship between increased body mass index (BMI) and an increased risk for breast cancer among postmenopausal women. However, most studies have found a decreased risk for premenopausal breast cancer. This study was conducted to find out the different effects of BMI on the risk of breast cancer among premenopausal and postmenopausal women, and explore the potential factors that influence the associations.MethodsA dose-response meta-analysis with 3,318,796 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 59 publications
4
64
2
2
Order By: Relevance
“…Studies have shown a positive association between BMi and an increased incidence of breast cancer in postmenopausal women. no positive correlation was found in premenopausal European women between BMi and breast cancer (34).…”
Section: Obesity and Cancermentioning
confidence: 82%
“…Studies have shown a positive association between BMi and an increased incidence of breast cancer in postmenopausal women. no positive correlation was found in premenopausal European women between BMi and breast cancer (34).…”
Section: Obesity and Cancermentioning
confidence: 82%
“…With regard to reproductive stage, there appears to be convincing evidence of a positive association between obesity and increased risk of post‐menopausal BC (Chen et al, ; Chen et al, ; Munsell et al, ; Xia et al, ). Interestingly, stratification by hormone receptor status suggests a consistent positive association for ERα+/PR+ BC, but no trend for ERα−/PR− cases (Munsell et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results indicate that obesity may influence the risk of pre‐menopausal BC based on hormone receptor status. In post‐menopausal women, epidemiological studies consistently report a positive association between BC and obesity (Chen et al, ; Chen et al, ; Munsell et al, ; Xia et al, ). An overweight (>25 kg·m −2 ) and obese (>30 kg·m −2 ) BMI are positively associated with BC incidence (Xia et al, ).…”
Section: Adiposity and Bcmentioning
confidence: 99%
See 2 more Smart Citations